Mycoplasma haemolamae and intestinal parasite relationships with erythrocyte variables in clinically healthy alpacas and llamas. (27th August 2019) - Viesselmann, Lisa C.; Videla, Ricardo; Schaefer, John; Chapman, Aly; Wyrosdick, Heidi; Schaefer, Deanna M. W.
Abstract: Background: Mycoplasma haemolamae (Mhl) and gastrointestinal nematodes can cause anemia in camelids. Control programs aim to suppress parasitism without promoting anthelminthic resistance, but few evidence‐based guidelines define acceptable parasite loads in camelids. Hypothesis/Objectives: In clinically healthy nonanemic camelids, compare erythrocyte variables to Mhl real‐time PCR status and to fecal egg count (FEC). Determine the FEC threshold above which erythrocyte variables are consistently below reference interval medians. Animals: One hundred fourteen client‐owned adult alpacas and llamas. Methods: In a cross‐sectional study, whole blood in ethylenediaminetetraacetic acid (EDTA) was assessed for packed cell volume (PCV) by centrifugation, erythrocyte count (RBC), and hemoglobin concentration (HGB) using an ADVIA120 analyzer, and Mhl using real‐time PCR. Trichostrongyle eggs per gram (epg) were counted by modified McMaster test on freshly collected feces. Significant differences in erythrocyte variables based on Mhl status and FEC thresholds were assessed by independent t test and one‐way ANOVA, respectively. Results: Packed cell volume, RBC, and HGB were not significantly different between Mhl‐positive and Mhl‐negative animals, but were significantly lower in animals with FEC >1000 epg compared to those with <500 epg. All animals with FEC >600 epg had RBC and HGB below the reference interval median. All animals with FEC >750 epg had PCV below the reference interval median. Conclusions and Clinical Importance: In healthy nonanemic camelids, positive Mhl PCR is not associated with lower erythrocyte variables and such animals may not warrant treatment. Fecal egg count >600‐750 epg has a negative effect on erythrocyte variables, and may be a guide for deworming protocols.